DETERMINANT FACTORS ANALYSIS OF BANK PROFITABILITY: STUDY ON INDONESIAN BANKS PERIOD 2019-2022 - Raja Bayu Saragih, Alphin
The banking sector is one of the most important financial institutions in the Indonesian economy. Banks are the significant driver of economic growth by delivering capital toward productive investments. Thus, banks must be profitable to continue operating and support economic growth. This study investigates the relationship between bank-specific determinants of Bank Size (SIZE), Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Operating Cost to Operating Income (OCOI), and Nonperforming Loans (NPL) toward Bank Profitability measured by Return on Asset (ROA). The research uses data from 10 Indonesian banks in KBMI 3 and 4 categories from 2019 – 2022. Classical assumption tests are run to ensure the data is considered BLUE. The study used Fixed Effect Model panel data regression. The research results show that CAR has a positive insignificant relationship toward ROA while LDR has positive significant relationship toward ROA. In contrast, SIZE, OCOI, and NPL have a negative significant relationship toward ROA. Due to the SIZE, LDR, OCOI, and NPL show a significant relationship with ROA, this study has recommendations for bank management to pay more attention to these variables to maintain the banks’ ROA.